Onye Agbataobim (My Neighbour) – One Who Finds Refuge in My Heart: On the Significance of Igbo Theological Anthropology for Theological Education in our Time (Keynote Address) - Atansi, Chukwuemeka Anthony (Journal of the Council for Research on Religion)

(untitled) (Council for Research on Religion, 2023)
In fashioning a response to the question “Who is my neighbour?” – which informs the subject of the symposium on “Theological Education in the Global Village of the 21st Century” – this essay explores the contributions of the Igbo theological anthropology of the neighbour. Igbo theological anthropology considers the neighbour, not simply as one with whom my home shares a boundary, but as one who finds refuge in my heart (onye agbataobim), that is, one with whom there is mutual dependence, vulnerability, and support. This relational understanding of the neighbour in Igbo theological anthropology further derives from the Igbo conception of the human person as “the beauty of life” (mmadụ), and the corresponding attitude of love, “the act of beholding” (ịfunanya), which the sight of, or rather, the encounter with every human person, ought to evoke. The article will outline the significance of these insights for theological education in our time. Such education, the essay argues, ought to take seriously again the fact that there is something irreducibly astonishing about the human person – each and every human being – regardless of geographical boundaries, physical proximity, as well as social, political, and economic connections.